2015
DOI: 10.1371/journal.ppat.1005288
|View full text |Cite
|
Sign up to set email alerts
|

The Transcription and Translation Landscapes during Human Cytomegalovirus Infection Reveal Novel Host-Pathogen Interactions

Abstract: Viruses are by definition fully dependent on the cellular translation machinery, and develop diverse mechanisms to co-opt this machinery for their own benefit. Unlike many viruses, human cytomegalovirus (HCMV) does suppress the host translation machinery, and the extent to which translation machinery contributes to the overall pattern of viral replication and pathogenesis remains elusive. Here, we combine RNA sequencing and ribosomal profiling analyses to systematically address this question. By simultaneously… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
97
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(107 citation statements)
references
References 65 publications
9
97
0
Order By: Relevance
“…No transcriptional start sites within the UL138 cds have been mapped (11,33,37), and inhibiting translation initiation at codon 1 by mutation does not preclude the production of pUL138-S (Fig. 2C).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…No transcriptional start sites within the UL138 cds have been mapped (11,33,37), and inhibiting translation initiation at codon 1 by mutation does not preclude the production of pUL138-S (Fig. 2C).…”
Section: Discussionmentioning
confidence: 99%
“…Our current study demonstrates that the two protein isoforms of pUL138 may have both overlapping and distinct functions during HCMV infection. In recent years, many studies have contributed to a body of work that begins to effectively demonstrate the power and function of increased coding capacity in HCMV through transcriptional, translational, and posttranslational mechanisms (9,15,32,33,37,58,59). Further, many examples of viral protein isoforms that have similar or unique functions exist (60)(61)(62)(63)(64)(65)(66)(67), but these examples likely only begin to scratch the surface of the important roles that protein isoforms play in viral infection and virus-host interactions.…”
Section: Identified Cd8mentioning
confidence: 99%
See 1 more Smart Citation
“…Attempts to distinguish discrete roles for conjugated versus unconjugated ISG15 have so far been equivocal in HCMV-infected cells (33; C. Bianco and I. Mohr, unpublished observations). Finally, because ISGylation occurs cotranslationally (10), HCMV might further influence host proteins targeted for ISG15 conjugation by regulating which host mRNAs are associated with polyribosomes (22,29). Excluding mRNAs from polyribosomes that code for antiviral proteins whose activities might be augmented by cotranslational ISGylation would limit the impact of ISG15 conjugation on HCMV replication.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, ribosome profiling can also simultaneously reveal the translation of host mRNAs during a viral infection. In a recent study, translational changes in host genes upon HCMV infection were studied by simultaneous transcriptome sequencing (RNA-Seq) and ribosome profiling (17). That study revealed many host genes translationally activated or repressed by HCMV, which does not induce a host shutoff.…”
mentioning
confidence: 99%